Expression pattern of the fused in sarcoma gene and its contextual influence on the density-specific response of the growth hormone/insulin-like growth factor 1 axis in zig-zag eels (Mastacembelus armatus) - Xue, Lingzhan; Gao, Yu; Zhang, Songpei; Weng, Manxin; Zeng, Gaoxiong; Chen, Jiajia; Liao, Mengxiang; Alavi, Sayyed Mohammad Hadi; Guiguen, Yann (Frontiers in Marine Science, 2024)
The fused in sarcoma (FUS) protein is a DNA/RNA binding protein from the ten-eleven translocation protein family that is associated with neurodegeneration, and it has been shown to promote cell proliferation through the growth hormone/insulin-like growth factor 1 (Gh/Igf-1) signaling pathway. The zig-zag eel (Mastacembelus armatus) is a newly discovered species exhibiting sexual dimorphism in growth, and the potential role of fus in the growth and development of this species remains largely unknown. Herein, we analyzed the homology, conserved domains, evolutionary characteristics, and conserved syntenies of fus in several teleost species. The expression of fus was predominant in the brain and exhibited sexual dimorphism in the brain, muscle, and liver of zig-zag eels. We found that microRNA (miR)-146-5p, miR-489-3p, and 24 other miRNAs were targeted to the fus 3′ untranslated region, which might affect muscle and bone development in adults. The igf1, insulin-like growth factor 1 receptor a (igf1ra), insulin-like growth factor 2 receptor (igf2r), growth hormone-releasing hormone-like receptor (ghrhrl), growth hormone secretagogue receptor type 1 (ghsr), and glucocorticoid receptor (gr) genes contained a higher abundance of GU-rich fus motifs compared to the other four genes analyzed in zig-zag eels. We also measured the expression of fus mRNA during fish culture at various stocking densities to further elucidate the relationship between fus expression and the Gh/Igf-1 axis. After 100 days of fish cultivation, the expression of fus and ghrhrl decreased and the expression of ghrh and gr increased as the culture density increased (p < 0.05). The expression of fus exhibited a remarkable positive correlation with a specific growth rate. These results indicate that fus mediates growth differences by regulating the expression of several growth-related genes including Gh/Igf-1 axis genes in zig-zag eels.